Design de mobiliário urbano para espaços verdes : estudos da utilização da cortiça - Teixeira, Rita, 1992- (2017)
This thesis, untitled Urban furniture design for green spaces - study the use of cork, aims to study a new way of being and experiences of citizens in the urban space by proposing a multipurpose street furniture that suits green spaces. Urban space should be seen as a place of coexistence and leisure, as well as services and streams. Today, due to the current period of technological change, the role of public space has changed, as a means of communication and information, as well as in leisure and leisure uses. One of the elements present in this space is the urban furniture and is it that focuses more on the development of this work. Through the study of the materials used in urban furniture, it could analyze and conclude on the potential and valences of cork material. This material has an important significance for the country's economy in a market leading position, since Portugal is the producer with more than half of the world share. It also held a contextualization within the cork industry in Portugal and its prospects for the future. Then, a market study on the various applications of cork is presented within the areas of design, architecture, fashion, sports and aerospace, which helps to understand the ability to apply this material. Through a synthesis, they are some of the possible applications of cork in street furniture, being a material constant study. Finally, to present a proposal of an urban equipment for the public space as a response to the needs detected in the use of the green spaces surrounding museums and other cultural centres, which proposes a possibility of application of this material in this context, which until now it has not been very usual